Performance Evaluation of Porous Pavement Concrete Incorporating Recycled Construction and Demolition Aggregates - Ximenes, José; Aguiar, José; Pais, Jorge; de Jesus, Carlos; Palha, Carlos (Indonesian Journal Publisher, 2026)
The objective of this study is to develop porous cement concrete for road pavements using construction waste aggregates to achieve the required surface characteristics. The research method in this study was laboratory experiments involving a series of concrete mixtures with varying waste content between 10% and 30%. Meanwhile, the cement content and water/cement ratio remained constant, based on previous studies in which the effects of these variables had been evaluated. The results of this study show that the performance of porous cement concrete has undergone two types of permeability evaluation tests, laser measurements for flatness and texture analysis, and the British Pendulum Test for friction evaluation. The aggregate gradation follows the PA12.5 specification, with a maximum aggregate size of 14 mm, serving as a reference concrete without recycled aggregates. Mechanical strength tests were included in the performance evaluation to measure the durability of the concrete. The findings of this study indicate that porous cement concrete containing demolition waste is a viable and sustainable solution for managing demolition waste materials.